MATHEMATICAL REPRESENTATION OF GRADE 7 STUDENTS IN SET THEORY TOPICS THROUGH PROBLEM-BASED LEARNING - Ida Lestari; Nila Kesumawati; Yunika Lestaria Ningsih (Jurnal Infinity, 2020)
Set theory has a wide role in mathematical concepts. Students have to understand the set theory before learning other concepts such as algebra and probability. This study aims to determine the effect of the problem-based learning (PBL) model on the students’ mathematical representation in set theory topics. The method used in this study is a quasi-experiment design. The populations in this study were 289 students of 7th grade at Secondary School in Palembang. The sample of this study were students of class 7.8 (control group) and 7.10 (experimental group). Data were collected through tests, interviews, and documentation. Based on data analysis, known that PBL affects the students’ mathematical representation. Students who had the PBL model get the better score of mathematical representation. They could use the symbol of set correctly, represent the set into Venn diagram correctly and they also could explain their answer. Furthermore, the implementation of the PBL model is offered.